![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(A=\left(1+3+3^2\right)+3^3\left(1+3+3^2\right)+...+3^{96}\left(1+3+3^2\right)\)
\(=13+3^3.13+...+3^{96}.13\)
\(=13\left(1+3^3+...+3^{96}\right)⋮13\)
\(A=\left(1+3+3^2\right)+\left(3^3+3^4+3^5\right)+...+\left(3^{96}+3^{97}+3^{98}\right)\\ A=\left(1+3+3^2\right)+3^3\left(1+3+3^2\right)+...+3^{96}\left(1+3+3^2\right)\\ A=\left(1+3+3^2\right)\left(1+3^3+...+3^{96}\right)\\ A=13\left(1+3^3+...+3^{96}\right)⋮13\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(S=\left(1+3+3^2\right)+3^3\left(1+3+3^2\right)+...+3^{96}\left(1+3+3^2\right)\)
\(=13+3^3.13+...+3^{96}.13=13\left(1+3^3+...+3^{96}\right)⋮13\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(1,Y=\left(1+3+3^2\right)+\left(3^3+3^4+3^5\right)+...+\left(3^{96}+3^{97}+3^{98}\right)\\ Y=\left(1+3+3^2\right)\left(1+3^3+...+3^{96}\right)\\ Y=13\left(1+3^3+...+3^{96}\right)⋮13\\ 2,A=\left(1+3\right)+\left(3^2+3^3\right)+...+\left(3^{2018}+3^{2019}\right)\\ A=\left(1+3\right)\left(1+3^2+...+3^{2019}\right)\\ A=4\left(1+3^2+...+3^{2019}\right)⋮4\\ 3,\Leftrightarrow2\left(x+4\right)=60\Leftrightarrow x+4=30\Leftrightarrow x=36\)
![](https://rs.olm.vn/images/avt/0.png?1311)
`#3107.101107`
\(A = 1 + 3 + 3^2 + 3^3 + ... + 3^{98} + 3^{99}\)
\(A = (1 + 3) + (3^2 + 3^3) + ... + (3^{98} + 3^{99})\)
\(A = (1 + 3) + 3^2(1 + 3) + ... + 3^{98}(1 + 3)\)
\(A = (1 + 3)(1 + 3^2 + ... + 3^{98})\)
\(A = 4(1 + 3^2 + ... + 3^{98})\)
Vì \(4(1 + 3^2 + ... + 3^{98}) \) \(\vdots\) \(4\)
`\Rightarrow A \vdots 4`
Vậy, `A \vdots 4` (đpcm).
A = 1 + 3 + 32 + 33 + ... + 398 + 399
A = (1 + 3) + (32 + 33) + ... + (398 + 399)
A = 1. (1 + 3) + 32. (1 + 3) + ... + 398. (1 + 3)
A = 1.4 + 32.4 + ... + 398.4
A = 4. (1 + 32 + ... + 398)
⇒ A ⋮ 4
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) P = 1 + 3 + 3² + ... + 3¹⁰¹
= (1 + 3 + 3²) + (3³ + 3⁴ + 3⁵) + ... + (3⁹⁹ + 3¹⁰⁰ + 3¹⁰¹)
= 13 + 3³.(1 + 3 + 3²) + ... + 3⁹⁹.(1 + 3 + 3²)
= 13 + 3³.13 + ... + 3⁹⁹.13
= 13.(1 + 3³ + ... + 3⁹⁹) ⋮ 13
Vậy P ⋮ 13
b) B = 1 + 2² + 2⁴ + ... + 2²⁰²⁰
= (1 + 2² + 2⁴) + (2⁶ + 2⁸ + 2¹⁰) + ... + (2²⁰¹⁶ + 2²⁰¹⁸ + 2²⁰²⁰)
= 21 + 2⁶.(1 + 2² + 2⁴) + ... + 2²⁰¹⁶.(1 + 2² + 2⁴)
= 21 + 2⁶.21 + ... + 2²⁰¹⁶.21
= 21.(1 + 2⁶ + ... + 2²⁰¹⁶) ⋮ 21
Vậy B ⋮ 21
c) A = 2 + 2² + 2³ + ... + 2²⁰
= (2 + 2² + 2³ + 2⁴) + (2⁵ + 2⁶ + 2⁷ + 2⁸) + ... + (2¹⁷ + 2¹⁸ + 2¹⁹ + 2²⁰)
= 30 + 2⁴.(2 + 2² + 2³ + 2⁴) + ... + 2¹⁶.(2 + 2² + 2³ + 2⁴)
= 30 + 2⁴.30 + ... + 2¹⁶.30
= 30.(1 + 2⁴ + ... + 2¹⁶)
= 5.6.(1 + 2⁴ + ... + 2¹⁶) ⋮ 5
Vậy A ⋮ 5
d) A = 1 + 4 + 4² + ... + 4⁹⁸
= (1 + 4 + 4²) + (4³ + 4⁴ + 4⁵) + ... + (4⁹⁷ + 4⁹⁸ + 4⁹⁹)
= 21 + 4³.(1 + 4 + 4²) + ... + 4⁹⁷.(1 + 4 + 4²)
= 21 + 4³.21 + ... + 4⁹⁷.21
= 21.(1 + 4³ + ... + 4⁹⁷) ⋮ 21
Vậy A ⋮ 21
e) A = 11⁹ + 11⁸ + 11⁷ + ... + 11 + 1
= (11⁹ + 11⁸ + 11⁷ + 11⁶ + 11⁵) + (11⁴ + 11³ + 11² + 11 + 1)
= 11⁵.(11⁴ + 11³ + 11² + 11 + 1) + 16105
= 11⁵.16105 + 16105
= 16105.(11⁵ + 1)
= 5.3221.(11⁵ + 1) ⋮ 5
Vậy A ⋮ 5
![](https://rs.olm.vn/images/avt/0.png?1311)
S = ( 3 + 32 +33)+(34+35+36) + (37+38+39)
S = 3.(1+3+9)+34.(1+3+9)+37.(1+3+9)
S = 3.13 + 34.13+37.13
S = 13.(3+34+37) ⋮13 ( đpcm)
Tick cho mình
`#3107.101107`
`S = 3 + 3^2 + 3^3 + ... + 3^9`
`= (3 + 3^2 + 3^3) + ... + (3^7 + 3^8 + 3^9)`
`= 3(1 + 3 + 3^2) + ... + 3^7(1 + 3 +3^2)`
`= (1 + 3 + 3^2)(3 + ... + 3^7)`
`= 13(3 + ... + 3^7)` $\vdots 13$
$\Rightarrow S \vdots 13.$
![](https://rs.olm.vn/images/avt/0.png?1311)
\(S=\left(1+3+3^2\right)+...+3^7\left(1+3+3^2\right)\)
\(=13\left(1+...+3^7\right)⋮13\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(A=3+3^2+3^3+...+3^{99}\\ \Rightarrow A=\left(3+3^2+3^3\right)+\left(3^4+3^5+3^6\right)+...+\left(3^{97}+3^{98}+3^{99}\right)\\ \Rightarrow A=3\left(1+3+3^2\right)+3^4\left(1+3+3^2\right)+...+3^{97}\left(1+3+3^2\right)\\ \Rightarrow A=\left(1+3+3^2\right)\left(3+3^4+...+3^{97}\right)\\ \Rightarrow A=13\left(3+3^4+...+3^{97}\right)⋮13\)
\(A=3+3^2+3^3+...+3^{99}\\ 3A-A=3^{99}-1\\ A=\dfrac{3^{99}-1}{2}\)